2020
DOI: 10.3390/su12051754
|View full text |Cite
|
Sign up to set email alerts
|

Community Acceptance of Wind Energy Developments: Experience from Wind Energy Scarce Regions in Europe

Abstract: Renewable energy plays an important role in the transition to a low emission society, yet in many regions energy projects have resulted in increasing societal polarization. Based on a comprehensive literature review and a survey among stakeholders from specific regions in Germany, Italy, Latvia, Norway, Poland and Spain with little prior experience with wind energy, we highlight six categories of factors that shape community acceptance of onshore wind energy development: technical characteristics of wind energ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 44 publications
2
34
0
Order By: Relevance
“…It would be characterized by the small number of business owners and a non-integrated legal system, which has not allowed the participation of other types of shareholders, favoring the interests of corporative networks [44,55,56]. Our results are compatible with the findings of Leiren et al [26] because the analysis of the available information clearly shows a model in which the promoting companies are extremely active in wind power. The result is that ownership of authorized wind farms in Galicia is, mainly, in the hands of multinational business groups, who are involved in energy, banking and diverse investments.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…It would be characterized by the small number of business owners and a non-integrated legal system, which has not allowed the participation of other types of shareholders, favoring the interests of corporative networks [44,55,56]. Our results are compatible with the findings of Leiren et al [26] because the analysis of the available information clearly shows a model in which the promoting companies are extremely active in wind power. The result is that ownership of authorized wind farms in Galicia is, mainly, in the hands of multinational business groups, who are involved in energy, banking and diverse investments.…”
supporting
confidence: 89%
“…The authors investigated people's attitudes towards wind power in Germany and Poland, using key variables such as type of ownership, degree of local participation in the planning process, distribution of turbines across regions, and the motivation for developing wind power. Leiren et al [26] (to highlight the information in Table 2 on page 6) identified the key factors in acceptance-related patterns of wind energy development, emphasizing the degree of local ownership of the wind farms of the impacts on economy: local community stakeholders enjoy "higher levels of trust than commercial developers, which are not usually embedded locally" (page 18) and help to generate local added value and "contribute to a more democratic energy system and social economic development"(page 18). Regueiro and Doldán [37] explain that the participation of all the agents involved and landowners or small investors as shareholders are some of the key factors in policy developing wind energy in Europe.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This figure also represents the framework for the expert assessments carried out in the frame of the WinWind project. Within the framework of the WinWind project, similarities and differences between social acceptance patterns in selected wind energy scarce target regions have been analyzed [23,24]. Furthermore, a comparative expert assessment addressing stakeholders in the WinWind target regions was carried out, providing policy relevant insights about procedural and financial participation.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, community opposition has proven to be a central obstacle to the promotion of use of the wind energy in many regions across Europe. This is documented by a vast academic literature as well as by a number of cooperative European projects [2][3][4].…”
Section: Introductionmentioning
confidence: 99%